2019
DOI: 10.1634/theoncologist.2018-0747
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Risk of Premature Ischemic Stroke in 5-Year Survivors of Nasopharyngeal Carcinoma

Abstract: Background Research on cancer survivorship associated with nasopharyngeal carcinoma (NPC) is rare. We aimed to elucidate the risk of ischemic stroke in 5‐year survivors of NPC following radiotherapy (RT) or concurrent chemoradiation therapy (CCRT). Subjects, Materials, and Methods NPC survivors, defined as those who survived longer than 5 years after diagnosis, were identified and matched at a 1:5 ratio with normal controls from the Longitudinal Health Insurance Database 2005 of Taiwan. The stratified Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
3
20
1
Order By: Relevance
“…These results provide evidence that young OCC survivors (<50 years old) should not be exempt from stroke surveillance. Similar findings have been reported in nasopharyngeal carcinoma survivors, in whom radiation is the main treatment modality [7][8][9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results provide evidence that young OCC survivors (<50 years old) should not be exempt from stroke surveillance. Similar findings have been reported in nasopharyngeal carcinoma survivors, in whom radiation is the main treatment modality [7][8][9].…”
Section: Discussionsupporting
confidence: 86%
“…Due to advances in surgical and radiation technology, the number of male OCC survivors is expected to increase from around 250,000 people in 2020 to over 300,000 in 2030 [3]. Previous studies have suggested that there may be an increased risk of stroke in patients with head and neck cancers, and have proposed that radiation may cause this long-term complication [4][5][6][7][8][9]. However, head and neck cancer is a heterogeneous disease, and these studies have included all patients from diagnosis rather than specifically focusing on long-term survivors.…”
Section: Introductionmentioning
confidence: 99%
“…24 Increased non-cancer-related mortality in >5-year survivors is multifactorial but appears to be largely driven by cardiovascular disease (i.e., exacerbation of hypertension, increased risk of stroke, and myocardial infarction). 25 A Surveillance, Epidemiology and End Results (SEER) population-based study demonstrated a high comorbidity burden in HNC patients at the time of diagnosis which increased significantly at 5 years post-diagnosis; this trend was measured in both HPV-related and HPV-unrelated disease variants. 26 In addition to a higher rate of medical problems, HNC survivors have also been shown to demonstrate a nearly twofold risk (adjusted rate ratio, 1.97) of suicide over time compared to patients with other types of cancers.…”
Section: Survivorship Clinicmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is characterized by its unique geographic distribution in southeastern China and Taiwan, and both environmental factors and genetic traits contribute to its development [ 1 ]. Concurrent chemoradiation therapy (CCRT) prolongs survival in patients with NPC [ 2 , 3 ]. With the increased number of five-year cancer survivors, survivorship has become an important issue [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%